Distribution and Mixotrophy of Cryptophyte Phytoplankton in the Northern Gulf of Alaska - O'Hara, Megan (Western CEDAR, 2023)
The Northern Gulf of Alaska (NGA) is a productive subarctic marine ecosystem that supports high abundances of plankton, fishes, seabirds, and mammals. Research has shown that this high productivity is primarily controlled by seasonal and spatial heterogeneity in the lower trophic level food web. Marine cryptophytes are a crucial, yet understudied, phytoplankton group in the NGA. Cryptophytes have the capacity for mixotrophy (acquiring energy through photosynthesis and feeding) which can improve trophic transfer efficiency, increase cellular growth rates, and improve retention of nutrients in the water column. Field samples collected in spring, summer, and fall 2021 surveyed the contribution of marine cryptophytes to the phytoplankton community in the NGA and assessed how natural variability in environmental factors influenced their distribution and mixotrophic capabilities. Our study demonstrated high spatial and temporal variability in cryptophyte biomass and community composition across the NGA. Cryptophytes were found in highest abundances in summer and fall, with smaller cells (3- 10 μm) dominating the cryptophyte community composition during the summer in nearshore waters and larger cells (10-25 μm) playing an important role offshore in the fall. This variability, along with a capacity to live in a wide range of environmental conditions in the NGA, suggests that cryptophytes are versatile protists. Analysis of small cell-dominated phytoplankton communities generated carbon biomass estimates up to 600 μgC/L and carbon to chlorophyll ratios up to 300. These values were higher than previously expected for a small cell community in the NGA and indicated high carbon transfer potential from small cells despite low chlorophyll concentrations in some seasons. Cryptophytes and other nanoeukaryotes consistently made up ~75 % of the total phytoplankton community biomass in summer and fall in the NGA. This research suggests that cryptophytes are a critical component of the lower trophic level food web in the NGA in ...